How many genetic options for evolving insecticide resistance in heliothine and spodopteran pests? - John G. Oakeshott; Claire A. Farnsworth; Peter D. East; Colin Scott; Yangchun Han; Yidong Wu; Robyn J. Russell (2013)
The widely accepted paradigm for the development of insecticide resistance in field populations of insects is of selection for one or a very few genes of major effect. Limited genetic mapping data for organophosphate and pyrethroid resistance in heliothine and spodopteran pests generally agrees with this paradigm. However, other biochemical and transcriptomic data suggest a more complex set of changes in multiple P450 and esterase gene/enzyme systems in resistant strains of these species. We discuss possible explanations for this paradox, including the likely embedding of these genes in regulatory cascades and emerging evidence for their arrangement in large clusters of closely related genes. We conclude that there could indeed be an unusually large number of genetic options for evolving resistance in these species.